The Impact of Metacognitive Reading Strategies on Master Students’ EFL Reading Proficiency and Academic Achievement - Levchyk, Iryna; Chaikovska, Hanna; Mazur, Oksana; Adamska, Zoriana; Zakordonets, Nataliia (Acta Paedagogica Vilnensia, 2022)
The paper investigates correlation of learners’ academic achievements with the application of metacognitive reading strategies (MRS) by the master students in EFL academic reading activities. The study was conducted in Ternopil Volodymyr Hnatiuk National Pedagogical University. Data was collected by means of focus groups interview and adapted scales of the MARSI questionnaire. The highlighted research is of a descriptive character; it has been completed with the aim of collecting the information at the initial stage of the experiment on master students’ usage of MRS in EFL academic reading activities.
Keywords: metacognitive reading strategies; reading comprehension; academic achievement